Body language: Its importance for communication with horses - Ladewig, J. (Journal of Veterinary Behavior Clinical Applications and Research, 2019)
Body language is important for communication between individuals. Body language is based on the fact that the thought of performing a known action, alone, will activate the motor neurons used for the action, resulting in a slight contraction of the involved muscles. These contractions are called intention movements and signal what the sender will do within the next second, enabling the recipient to react. This type of communication is important both for animals and for peoples' interaction with animals. For example, for social animals, body language communication during competitive situations may prevent subsequent physical interaction making life in the social group more peaceful. Domestic animals that have frequent contact with people learn to read human body language. Similarly, experienced animal trainers learn to read the body language of their animals. This exchange of information makes it safer and more efficient to work with horses. The subtleties of body language may also influence results of scientific studies. Research on preferences or cognitive abilities in horses often use choice experiments combined with operant conditioning. Recent studies have thus demonstrated that horses prefer larger quantities of food than smaller quantities, that they have prospective memory, and that they can communicate with people using symbols. These results may be true, but because the experimental horses are handled by people right before they make their choice within the experiment, it is not possible to determine whether their choice is their own or whether it has been influenced by the body language of the handlers. To be valid, this kind of experiment must eliminate any possibility of human influence. In conclusion, better awareness of horses' body language as well as our own body language makes work with horses easier, safer, and more efficient. Furthermore, creating an environment in which foals and young horses are properly socialized will prepare them for an adult life in a social group, something that is a prerequisite for acceptable horse welfare.